El desempleo de largo plazo en el AMCO. Confluencia de fenómenos de histéresis, migración y recomposición sectorial. (2021)
This Work presents some general considerations about the unemployment rate in a long term in the AMCO and consider its behavior in the last 20 years. It shows that the factor associated to the evolution of such labor variable have to do with the hysteresis phenomena , the demographic dynamics, migrations processes and the sectorial recomposition in the metropolitan economy.